Parcelamento da adubação nitrogenada sobre o crescimento e produção de alho ‘Branco Mossoró' - Paiva, Laíza Gomes de (Universidade Federal Rural do Semi-Árido, 2019)
The management of nitrogen fertilization in the garlic crop can provide gains in productive and economic terms to the producer, as well as to the environment. In the case of common garlic, research is still scarce on this subject. The objective of this work was to evaluate the effects of fractionation of nitrogen fertilization on the growth and production of 'Branco Mossoró' garlic. The experiment was carried out at the Horta do Departmento de Ciências Agronômicas e Florestais, Centro de Ciências Agrárias da Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró-RN. On the analysis of the growth, it was used experimental design in randomized plots with four repetitions. The treatments were arranged in subdivided plots, the plots being represented by nitrogen fertilization: Nitrogen applied at planting (90 kg ha-1), Nitrogen applied twice, being 1/3 at planting and 2/3 at 30 days after planting (DAP) and Nitrogen applied three times, being 1/3 at planting, 1/3 at 30 DAP and 1/3 at 60 DAP. The subplots were represented for plant sampling times at 45, 60, 75, 90, 105 and 120 DAP. To quantify the production, a randomized complete block design with repetitions was used, where each treatment was repeated twice in each block. For the growth characteristics, plant height; number of leaves; aerial parts, bulb and total dry mass accumulation; bulb ratio; absolute and relative increase ratio were assessed. For the characteristics of production, superbudding rate of plants, final stand, bulb average mass, bulb total production, bulb classification, commercial and non-commercial productivity. The fractionation of nitrogen fertilization allowed increase in plant height, aerial part and bulb dry mass, as well as absolute increase rate. Commercial and non-commercial productivity were influenced by the partionation of nitrogen fertilization
Keywords: Allium sativum; Nitrogênio; Taxa de crescimento; Rendimento; Allium sativum; Nitrogen; Growth rate; Efficiency; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA